Association between IL-38 and inflammatory indicators in patients with bacterial pneumonia. (January 2023) - Sun, Xiaoyu; Zhou, Jie; Huang, Wenjuan; Wang, Bo; Zhang, Yi; Duan, Liang; Chen, Weixian
Highlights: Serum IL-38 expression was elevated in patients with bacterial pneumonia. Serum IL-38 levels were negatively correlated with clinical inflammatory indicators. IL-38 attenuated LPS-induced IL-6, IL-8, IL-1β and TNF-α as well as ICAM-1 expression in BEAS-2B cells. IL-38 ameliorated the activation of STAT3 and NF-κB signaling pathways. IL-38 may serve as a potential biomarker for bacterial pneumonia. Abstract: Background: IL-38, a recently discovered cytokine of IL-1 family, exerts immunoregulatory activities in multi-type inflammatory diseases. However, its expression level and underlying clinical importance for IL-38 in respiratory bacterial infections remain unknown. Methods: Thirty-five patients with bacterial pneumonia and twenty age- and gender- matched healthy individuals were enrolled in the study to determine serum IL-38 concentrations by ELISA. Then, the correlation between serum IL-38 levels and clinical features were analyzed and ROC curve was used to evaluate the potential diagnostic value for bacterial infections. In vitro, LPS-stimulated human respiratory epithelial cell model was employed to explore immunomodulatory mechanism of IL-38 in pulmonary infections. Results: Elevated serum levels of IL-38 were determined in patients with bacterial pneumonia when compared with healthy controls. In addition, serum IL-38 levels were negatively correlated with clinical inflammation parameters, including WBC count, CRP, PCT and proinflammatory IL-6 and IL-8. In vitro, we demonstrated that recombinant IL-38 was able to remarkably inhibit expression of proinflammatory IL-6, IL-8, IL-1β and TNF-α as well as adhesion molecule ICAM-1, which were partially mediated by attenuated activation of STAT3 and NF-κB signal cascades in BEAS-2B cells. Furthermore, we identified the diagnostic efficiency of IL-38 in discriminating patients with bacterial pneumonia from healthy individuals. Conclusions: Our study indicates higher serum IL-38 levels in patients with bacterial pneumonia are involved in anti-inflammatory activities in respiratory infections revealing a critical role of IL-38 in attenuating excessive pulmonary inflammation against exogenous pathogens. More importantly, IL-38 exhibited a potential novel biomarker for bacterial pneumonia. Thus, our data may provide useful insights for both clinical and basic research for bacterial pneumonia diagnosis.